Expeditious damage index for arched structures based on dynamic identification testing - Giordano, Ersilia (2020)
This paper presents a new damage detection index for arched structures, which can easily and quickly provide an estimate of their integrity. The results from eight laboratory tests performed on both reinforced and unreinforced adobe arches are used to define the index. The arches are damaged up to collapse using pseudo-static test cycles carried out by applying progressive controlled displacements at third span. The test records allow to follow the stiffness degradation of each arch by plotting the relative force-displacement curves, as well as to track their frequencies variation during the damage evolution by means of dynamic identification tests performed at the end of each cycle. The new index considers the bending moment as the main cause of damage for the analysed arches; therefore, starting from the bending stiffness, a damage indicator was developed and experimentally validated, as function of the frequency reduction, respect to the undamaged scenario. Finally, the index is also validated for diferente types of arch collapse mechanisms through Finite Element Modeling.